2002
DOI: 10.1073/pnas.082101999
|View full text |Cite
|
Sign up to set email alerts
|

In vitro reconstitution and activity of a C/D box methylation guide ribonucleoprotein complex

Abstract: The genomes of hyperthermophilic Archaea encode dozens of methylation guide, C͞D box small RNAs that guide 2 -O-methylation of ribose to specific sites in rRNA and various tRNAs. The genes encoding the Sulfolobus homologues of eukaryotic proteins that are known to be present in C͞D box small nucleolar ribonucleoprotein (snoRNP) complexes were cloned, and the proteins (aFIB, aNOP56, and aL7a) were expressed and purified. The purified proteins along with an in vitro transcript of the Sulfolobus sR1 small RNA wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
226
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(241 citation statements)
references
References 43 publications
13
226
2
Order By: Relevance
“…[11][12][13][14] L7Ae protein binds directly to box C/D elements, 8,14 Nop5p binds to L7Ae, and fibrillarin serves as the core catalytic component. [15][16][17] This conserved structure is homologous to the box C/D snoRNP in eukaryotes, 16 which contains a K-turn snoRNA and four protein components. 18,19 Both sRNA and protein components are required in the methylation process.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] L7Ae protein binds directly to box C/D elements, 8,14 Nop5p binds to L7Ae, and fibrillarin serves as the core catalytic component. [15][16][17] This conserved structure is homologous to the box C/D snoRNP in eukaryotes, 16 which contains a K-turn snoRNA and four protein components. 18,19 Both sRNA and protein components are required in the methylation process.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, nop1.2, nop1.3, and nop1.7 mutations occurred in motif III, motif I, and motifs II and IV, respectively (9). Furthermore, by using an in vitro reconstituted archaeal sRNP enzyme, Omer et al (13) demonstrated that substitutions of two amino acids within motifs I and III of Sulfolobus solfataricus fibrillarin (A85V and P129V) resulted in completely or partially abolished methylation activities, whereas sRNP assembly was unaffected. These data suggest that fibrillarin has a function similar to other previously known AdoMet-dependent MTases.…”
mentioning
confidence: 99%
“…The modification is catalyzed by fibrillarin, one of three protein components of the box C͞D RNP in archaea (2,4,8). The other two box C͞D RNP proteins are L7Ae (a multifunctional RNA binding protein that is also a component of the ribosome and of box H͞ACA pseudouridylation guide RNPs) and Nop56͞58 (2,4,8,9). More than 50 box C͞D RNAs are encoded in the genomes of humans and Pyrococcus furiosus (1,2,4).…”
mentioning
confidence: 99%
“…The RNAs are characterized by the presence of one or two sets of the short, conserved sequence elements termed box C and box D. Base-pairing of the guide region of a box C͞D RNA to the target RNA establishes a site of 2Ј-O-methylation of the target RNA. The modification is catalyzed by fibrillarin, one of three protein components of the box C͞D RNP in archaea (2,4,8). The other two box C͞D RNP proteins are L7Ae (a multifunctional RNA binding protein that is also a component of the ribosome and of box H͞ACA pseudouridylation guide RNPs) and Nop56͞58 (2,4,8,9).…”
mentioning
confidence: 99%